Conjugated nanomaterials for solar fuel production. Issue 2 (4th January 2021) - Aitchison, Catherine M.; Sprick, Reiner Sebastian
Abstract : Photocatalytic hydrogen production from water has the potential to fulfil future energy needs by producing a clean and storable fuel. Here the discuss the recent advances in using nanosized materials as photocatalysts. Abstract : Photocatalytic hydrogen production from water has the potential to fulfil future energy needs by producing a clean and storable fuel. In recent years polymer photocatalysts have attracted significant interest in an attempt to address these challenges. One reason organic photocatalysts have been considered an attractive target is their synthetic modularity, therefore, the ability to tune their opto-electronic properties by incorporating different building blocks. A wide range of factors has been investigated and in particular nano-sized particles have found to be highly efficient due to the size effect resulting from the ability of these to increase the number of charges reaching catalytic sites.